Pharyngeal Stenosis and Swallowing Dysfunction Following Laryngectomy: A Scoping Review - Akash Halagur; Amar Sheth; Shannon Wu; Michael Belsky; Edward J. Damrose (Surgeries, 2025)
Background: Pharyngeal stenosis (PS) is a common sequela of a total laryngectomy (TL), and the most common cause of postoperative dysphagia. Its exact incidence is not known. A greater understanding of this clinical complication could serve to better inform patients considering a laryngectomy. Objective: Pharyngeal stenosis (PS) is a common sequela of a total laryngectomy (TL) and causes dysphagia. This systematic review aims to characterize PS as a sequela of a TL, specifically the incidence of dysphagia requiring dilation, and the frequency/timing of dilation interventions. Data Sources: We used PubMed. Review Methods: A search of all studies from PubMed published from conception to January 2024 was conducted. Cohort studies reporting PS requiring dilation following a TL were included. Data were collected on the incidence, recurrence, median time from TL to dilation, TL indication, and reconstructive approach. Two evaluators independently performed the study screening and data collection; all the differences were resolved by a third evaluator. Results: Eleven studies met the inclusion criteria. A total of 1421 patients underwent a TL, of which 659 (46.4%) were salvage, 286 (20.1%) were the primary treatment, and 153 (10.8%) were the primary with an adjuvant treatment. A total of 255 patients underwent reconstruction, among whom 86 (33.7%) had regional and 169 (66.3%) had free flaps. The mean age at the time of the TL was 64.1 (range 20–87) years, with a male-to-female ratio of 3.4:1. The overall incidence of dysphagia after a TL requiring dilation was 26%. Of the 370 patients who required dilation, 69.4% required multiple procedures. The median time to the first dilation post-TL ranged from 9 to 24 months. The overall complication rate was 4.3%, including perforation, infection, and diminished tracheoesophageal voice quality. Conclusions: Approximately one in four patients developed stenosis requiring dilation after a TL, of which two out of three required repeat dilations. Major complications, though rare, were predominantly observed during the first few dilation procedures.